WAYS TO IMPROVE THE DEVELOPMENT AND MANAGEMENT OF FOREIGN ECONOMIC ACTIVITY AT INDUSTRIAL ENTERPRISES OF UZBEKISTAN - Asiljon Yulchiyev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article discusses the improvement of the economic and social status of the country through the development of exports at industrial enterprises of Uzbekistan, the development of practical proposals and recommendations for improving the standard of living and eliminating unnecessary shortcomings.